Le Chemin : Lire Objet. - Gallery Moving Space, Gent; Baladine-Hovald, Isabelle; Bertrand, Veronique; Brusselmans, Herman; Buchholzer, Marie; Clincke, Lut; Germonpre, Christiaan; Gueth, Francis; Guth, Didier; Lacoue-Labarthe, Philippe; Lutz, Philippe; Nancy, Claire; et al. (Gent : Gallery Moving Space, 1995)
Dejean, Michel ; Hungler, Francis ; Bruetschy, François ; Gangloff, Pierre ; Willaert, Paul ; Nicaise, Christine ; Samson, Anne ; Rul, Chris ; Le-Hoa, Catherine ; Meyer, Christopher ; Hert, Leon ; Danicher, Louis ; 't Kindt, Jacques ; Reyes, Lucia ; Kern, Erik ; Obrecht, Suzanne ; Charvolin, Philippe ; Gaube, Bernard ; Hoorne, Emiel ; Gangloff, Catherine
biografie
Le Chemin : Lire Objet, Gallery Moving Space, Gent, 2.12 - 17.12.1995
Frans
Nederlands
boek